Photocatalytic Carbonylation Strategies: A Recent Trend in Organic Synthesis - Singh, Jitender; Sharma, Shivani; Sharma, Anuj (Journal of organic chemistry, 2021)
In the last few decades, photocatalytic radical carbonylation strategies have received considerable attention as they are becoming a formidable tool in the toolbox of organic synthesis. These carbonylation strategies involve the incorporation of a carbon monoxide into organic molecules in an atom- and step-economical manner. Mostly, these strategies rely on the generation of an acyl radical as a key intermediate, which would be created via incorporation of CO molecule to an alkyl/aryl radical. The production of alkyl/aryl radical in these methodologies required either the high-intensity light-induced transition-metal (TM)-catalyzed systems or visible-light-induced photocatalytic systems that would be capable of mediating single electron transfer (SET) to the C(sp )- or C(sp )-hybridized coupling partners. Here, in this review, the development in the field of photocatalytic carbonylation is described by compiling the literature of the last 40 years, and their reaction mechanisms have been emphatically discussed. In addition, to aid readers, we have assimilated redox potentials of photocatalysts and substrates for a better sense of spontaneity of these photoredox carbonylation reactions.